The effects of dynamic and static stretching exercises performed to elite wrestlers after high intensity exercise on heart rate variability - Yildirim, Y.; Arabaci, R.; Güngör, A. K.; Görülü, R. (Science & Sports, 2023)
Objectives Determining which recovery method is more effective for the athlete to maximize the level of recovery after the competition as soon as possible is important in terms of preparing the athlete for the next competition. We aimed to examine the effects of dynamic and static stretching exercises performed after work-out on the heart rate variability in elite wrestlers. Equipment and methods Twelve elite men freestyle wrestlers who continue training in Turkish Olympic Preparation Center (TOPC) in Bursa province (mean age 18.7 ± 1.5 years, weight 78.28 ± 13.0 kg, height 161.17 ± 46.1 cm), have participated in this study voluntarily. The study was completed on 3 different work-out day. Twelve participants were randomly divided into 3 groups. On the first work-out day, the same exercise program was applied to all 3 groups (6 minutes 30 seconds/one wrestling match time), then static stretching was applied to the 1st group, dynamic stretching to the 2nd group and passive resting to the 3rd group. On the second and third work-out days, the groups were moved crosswise. Thus, all participants applied all stretching exercises on 3 different days. During the exercise program and stretching exercises, heart rate variability of all participants was recorded with a Polar v800. Analyzes were performed with SPSS for Windows 23.0 (SPSS Inc, Chicago, USA) statistical program. Comparison of the differences was done by the Two Way ANOVA test. Bonferroni test was used for pairwise comparisons. Cohen's d value was used to determine the effect size (ES). Statistical significance was accepted as P < 0.05. Result and conclusion Significant differences were found between groups in RR triangular index, VLF, PNS index parameters. As a result of the study, it can be said that, among three different recovery methods after work-out, static stretching application increases VLF and PNS INDEX values and supports recovery in a shorter period.